Systematic proteome analysis identifies transcription factor YY1 as a direct target of miR-34a - Chen, Qing-Rong (2010)
MicroRNA 34a (miR-34a) is a potential tumor suppressor gene and has been identified as a miRNA component of the p53 network. To better understand the biological pathways involved in miR-34a action, a parallel global protein and mRNA expression profiling on miR-34a treated neuroblastoma cells (IMR32) was performed using isotope-coded affinity tags (ICAT) and Affymetrix U133plus2 microarray respectively. Global profiling showed that miR-34a causes much smaller mRNA expression changes compared to changes at the protein level. A total of 1495 proteins represented by 2 or more peptides were identified from the quantitative ICAT analysis, of which 143 and 192 proteins are significantly up- or down-regulated by miR-34a, respectively. Pathway analysis of these differentially expressed proteins showed the enrichment of apoptosis and cell death processes in up-regulated proteins but DNA replication and cell cycle processes in the down-regulated proteins. Ribosomal proteins are the most significant set down-regulated by miR-34a. Additionally, biological network analysis to identify direct interactions among the differentially expressed proteins demonstrated that the expression of the ubiquitous transcription factor YY1, as well as its downstream proteins, is significantly reduced by miR-34a. We further demonstrated that miR-34a directly targets YY1 through a miR-34a-binding site within the 3’ UTR of YY1 using a luciferase reporter system. YY1 is a negative regulator of p53 and it plays an essential role in cancer biology. Therefore, YY1 is another important direct target of miR-34a which closely regulates TP53 activities.